Genetics of Inherited Retinal Diseases in Understudied Populations - Kannabiran, Chitra; Parameswarappa, Deepika; Jalali, Subhadra (Frontiers in Genetics, 2022)
Retinitis pigmentosa is one of the major forms of inherited retinal dystrophy transmitted in all Mendelian and non-Mendelian forms of inheritance. It involves the loss of retinal photoreceptor cells with severe loss of vision or blindness within the first two decades of life. RP occurs at a relatively high prevalence in India and is often associated with consanguinity in South Asian communities where this practice is customary. Genetic studies on RP in India have been carried out with a range of methods aimed at detecting specific mutations, to screening of candidate genes or selected genomic regions, homozygosity mapping to whole genome sequencing. These efforts have led to a molecular genetic characterization of RP in Indian families. Similar studies on large extended families from Pakistan have provided insight into several novel genes underlying the pathogenesis of these diseases. The extreme degree of clinical ad genetic heterogeneity of RP renders it challenging to identify the associated genes in these populations, and to translate the research output towards better management of the disease, as there are no genetic features that are characteristic of any population so far.